2009
DOI: 10.1051/apido/2009022
|View full text |Cite
|
Sign up to set email alerts
|

Virgin queen execution in the stingless beeMelipona beecheii: The sign stimulus for worker attacks

Abstract: -Stingless bees produce considerable numbers of virgin queens over the year, most of which are superfluous and get executed by the workers. Nothing is known yet about the sign stimulus that releases the worker attacks. In the present study we investigated the queen execution process in Melipona beecheii and found in both behavioral observations and experiments with caged living virgin queens that workers are not attracted to them from a distance by means of volatile chemicals. Furthermore, worker aggression, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…On the 21st day after we established an orphan condition in our observation boxes, we observed a virgin queen (marked with color the first time we saw her) that was not aggressively attacked by the workers, as is typical during queen elimination in M. beecheii (Jarau et al, 2009). Instead, she actively contacted the workers and bumped into them, often bringing herself into close lateral contact with a worker and quickly shaking her abdomen in a wagging movement, thereby pushing the workers away.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…On the 21st day after we established an orphan condition in our observation boxes, we observed a virgin queen (marked with color the first time we saw her) that was not aggressively attacked by the workers, as is typical during queen elimination in M. beecheii (Jarau et al, 2009). Instead, she actively contacted the workers and bumped into them, often bringing herself into close lateral contact with a worker and quickly shaking her abdomen in a wagging movement, thereby pushing the workers away.…”
mentioning
confidence: 73%
“…Only little is known about the mechanism that releases the execution behavior in workers or about how a particular virgin queen is chosen as a new queen. Recently, we found that in Melipona beecheii a virgin queen's conspicuous behavior, which consists of rapidly running over the brood area, thereby making spinning movements and beating her wings, triggers the worker attacks (Jarau et al, 2009). A chemical signal or cue potentially released by such queens seems not to account for her execution.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…There may be other intrinsic factors related to the dominant behavior (Imperatriz-Fonseca & Zucchi 1995;Jarau et al 2009;Jarau et al 2010) such as patterns of cuticular hydrocarbons present in these bees (Nunes et al 2008) which interfere with the recognition of the individuals and are related to the process of acceptance of a new queen into the nest (Nunes et al 2009) or even group decision making regarding the choice of a new queen (Tarpy & Gilley 2004).…”
Section: Transfer Of the Larvae To The Production Of In Vitro Queensmentioning
confidence: 99%